PENGARUH SELF-EMPLOYED PARENTS, LATAR BELAKANG PENDIDIKAN, SELF-EFFICACY, PENGALAMAN KERJA DAN AKSES MODAL TERHADAP KEINGINAN BERWIRAUSAHA - Tri Hesti Utaminingtyas; Osly Usman; Suherman Suherman (Fakultas Ekonomi Universitas Negeri Jakarta, 2011)
Abstract This research aims at determining the influence of self-employed parents, education background, self efficacy, working experience and access to capital on entrepreneurial intention. Sample of this study comprises 300 students of State University of Jakarta (Universitas Negeri Jakarta - UNJ). The results show that self-efficacy, self-employed parents, and access to capital are important and significant factors affecting entrepreneurial intention. This results suggest directions for policy from UNJ that focus on instruments to enhance, specifically, students’ self-efficacy and access to capital. Keywords: entrepreneurial intention, self-employed parents, education background, self-efficacy, working experience, access to capital.